Statistical Validation of The Microplate Reader for Antioxidant Activity Measurement using The DPPH Assay - Rismawati, Rismawati; Kurnia, Dikdik; Hafiz, Ersanda; Zein, Muhammad Ihda H. L. (Chimica et Natura Acta, 2025)
Antioxidants research has been garnering increased interest among researchers, particularly in the fields of medicine and health, focusing on both natural and synthetic antioxidants. The DPPH method is the most used approach for antioxidant analysis due to its efficiency, simplicity, and accuracy. This study aims to validate the sensitivity of the microplate reader compared to UV-Vis spectrophotometer, both used for measuring absorbance in the DPPH antioxidant test. The samples used in this study include ascorbic acid, gallic acid, and quercetin standards. Statistical validation in the DPPH antioxidant test includes precision testing, T-test, and % recovery test. Based on the statistically analyzed results, the T-test values for ascorbic acid, gallic acid, and quercetin standards were 0.86, 1.52 and 0.20, respectively, all of which are less than the t-table value of 1.72. The T-test values being less than the t-table value indicates that there is no significant difference between the two methods, UV-Vis spectrophotometer and microplate reader. Meanwhile, the precision test (Horrat)r values for the two methods were 0.52, 0.33, and 0.34, respectively. These precision values (Horrat)r fall within the 0.3-1.5 range, indicating acceptable precision. Additionally, the % recovery test for gallic acid showed values in the 90-100% range, indicating that both methods possess good sensitivity. As a result, a microplate reader is equally reliable yet more practical (faster, high-throughput, smaller volumes), especially valuable for labs with limited resources.